Pengaruh Struktur Modal Dan Efisiensi Aset Terhadap Profitabilitas Pada PT Waskita Karya Tbk Tahun 2013–2024 - Oktavia Dewi Antika; Agus Suhartono (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. This study aims to determine the effect of capital structure as measured by the Debt to Equity Ratio (DER) and asset efficiency as measured by Fixed Asset Turnover (FATO) on profitability proxied by Return on Assets (ROA) at PT Waskita Karya Tbk for the period 2013–2024. This research employs a quantitative approach using descriptive and verificative methods. The data used are secondary data obtained from the company’s annual financial statements during the research period. The data analysis techniques applied include simple linear regression and multiple linear regression using statistical software. The results indicate that partially, Debt to Equity Ratio (DER) has a negative and significant effect on Return on Assets (ROA) with a t-value of −4.242 and a significance level of 0.002 (< 0.05). Meanwhile, Fixed Asset Turnover (FATO) has a positive and significant effect on Return on Assets (ROA) with a t-value of 2.901 and a significance level of 0.016 (< 0.05). Simultaneously, Debt to Equity Ratio (DER) and Fixed Asset Turnover (FATO) have a significant effect on Return on Assets (ROA) with an F-value of 10.992 and a significance level of 0.004 (< 0.05). These findings indicate that capital structure management and efficient utilization of fixed assets play an important role in enhancing corporate profitability